Structural behaviour of steel-timber composite (STC) beam-to-column connections with double angle web cleats subjected to hogging bending moment. (1st August 2019) - Nouri, F.; Valipour, H.R.; Bradford, M.A.
Highlights: Demonstrate structural performance of the steel-timber composite (STC) connections. Conduct tests on STC beam-to-column connections with angle web cleats. Evaluate strength and stiffness of the STC connections with angle web cleats. Compare behaviour of the STC with steel-concrete composite connections. Develop a component-based model for the STC beam-to-column connections. Abstract: This paper deals with an experimental study of steel-timber composite (STC) beam-to-column connections with double web angles, with the aim of developing an efficient composite flooring system that exhibits superior structural performance yet is simple and cost-effective from a construction perspective. The experimental program involved the testing of six cruciform subassemblies representing internal beam-to-column connections subjected to negative (hogging) bending moments. In four specimens, STC beams were connected to the flanges of a universal column by double web angles. Additionally, a specimen with bare steel beams and another specimen with steel-concrete composite (SCC) beams were fabricated and tested to provide benchmarks for comparing the structural behaviour of the STC with bare steel and SCC beam-to-column connections. It is shown that the STC connections exhibit semi-rigid behaviour with negative bending moment and rotation capacities larger than that of SCC connections. Lastly, an analytical model which is an extension of the existing component-based method is proposed for estimating the negative bending moment capacity of the STC connections with double web angles.